2001
DOI: 10.1046/j.1532-5415.2001.4911237.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Demographic, Functional, and Behavioral Characteristics with Activity‐Related Fear of Falling Among Older Adults Transitioning to Frailty

Abstract: Activity-related fear of falling was present in almost half of this sample of older adults transitioning to frailty. The significant association of activity-related fear of falling with demographic, functional, and behavioral characteristics emphasizes the need for multidimensional intervention strategies to lessen activity-related fear of falling in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
6
21

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(189 citation statements)
references
References 36 publications
8
154
6
21
Order By: Relevance
“…Falls are well recognized as precursors to fractures, increased functional disability, and the need for long-term institutional care (5,9,10,13). Falling is a marker of frailty, and fall prevention is a key to reducing poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls are well recognized as precursors to fractures, increased functional disability, and the need for long-term institutional care (5,9,10,13). Falling is a marker of frailty, and fall prevention is a key to reducing poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of physical injury, falls can lead to the individual becoming fearful of experiencing subsequent falls (12). In turn, this fear of falling syndrome often causes a voluntary limitation of mobility, a gradual decrease in functional independence, and ultimately an increased need for residential care (13). Therefore, the health implications of falls are enormous, with costs for fall-related fractures alone being estimated at well over US$10 billion (14).…”
mentioning
confidence: 99%
“…46,47 The presence of back, joint, or muscle pain has been found to increase the likelihood of fear of falling reports two to four times, almost double in comparison to the findings from healthy, community-dwelling older adults. 18,45,48 Jamison and colleagues 48 reported that the presence of more intense pain was significantly associated with increased fear of falling in adults with arthritis. The relationship of chronic pain to fall risk is a complex interaction of factors including sleep disturbances, decreased attention, social withdrawal, medication use, functional limitations, gait changes, presence of other chronic conditions, and limitation of activity.…”
Section: Relationship Of Pain and Falls-efficacy To Balance And Walkingmentioning
confidence: 99%
“…First, it is an independent predisposing factor in both reduced physical status (e.g., muscle performance, mobility, balance, and physical activity involvement) [45][46][47] and negative psychosocial effects (e.g., social isolation and depression). 42,44,45 With decreased mobility and increased social isolation, fall-risk factors accumulate. The evidence is clear that increased fear of falling restricts both daily functional activity and recreational activity.…”
Section: Relationship Of Pain and Falls-efficacy To Balance And Walkingmentioning
confidence: 99%
“…17 However, there is growing evidence that fear of falling significantly contributes to activity restriction among older people, which in turn leads to greater disability and loss of independence. 16 Fear of falling has been associated with lower activities of daily living scores, 18 slower gait, 19 use of a walking aid, 19 emotional depression, 18,19 and poor health status. 20 Moreover, fear of falling is greater among those who have experienced a fall 21 and increases with the number of falls experienced.…”
Section: Fear Of Fallingmentioning
confidence: 99%